Factor the following polynomial completely.
20x2 + 22xy + 6y2 =

20x^2 + 22xy + 6y^2 = 2(2x + y)(5x + 3y)

s

Question

Asked 3/16/2016 10:07:56 AM

Updated 3/16/2016 10:25:21 AM

1 Answer/Comment

Rating

8

20x^2 + 22xy + 6y^2 = 2(2x + y)(5x + 3y)

Added 3/16/2016 10:25:21 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/16/2016 10:25:53 AM]

3ay(a + 2y)2 =

Question

Updated 3/16/2016 9:48:08 AM

1 Answer/Comment

3ay(a + 2y)^2 = 3a^3y + 12a^2y^2 + 12ay^3

Added 3/16/2016 9:48:08 AM

This answer has been confirmed as correct and helpful.

Perform the indicated operation.
(2x - 4y)(2x + 4y) **Weegy:** 2x - 4y for x = 2 and y = 4; 2(2) - 4(4) = 4 - 16 = -12 **User:** Simplify.
x2(2x3 - 3) - 3x(x + 4) **User:** Write the nth term of the following sequence in terms of the first term of the sequence.
1, 8, 15, 22, . . . (More)

Question

Updated 3/16/2016 11:52:16 PM

4 Answers/Comments

(2x - 4y)(2x + 4y)

= 2x*2x - 4y*2x + 2x*4y - 4y*4y

= 4x^2 - 8xy + 8xy - 16y^2

= 4x^2 - 16y^2

= 2x*2x - 4y*2x + 2x*4y - 4y*4y

= 4x^2 - 8xy + 8xy - 16y^2

= 4x^2 - 16y^2

Added 3/16/2016 6:43:13 PM

This answer has been confirmed as correct and helpful.

x^2(2x^3 - 3) - 3x(x + 4)

= x^2*2x^3 - x^2*3 - 3x*x - 3x*4

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 12x

= x^2*2x^3 - x^2*3 - 3x*x - 3x*4

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 12x

Added 3/16/2016 6:43:57 PM

This answer has been flagged as incorrect.

Flagged by Andrew. [3/16/2016 11:52:21 PM]

Write the nth term of the following sequence in terms of the first term of the sequence 1, 8, 15, 22, . . . is 7n - 6.

The common difference = 22 - 15 = 7;

nth term = 1 + (n - 1)*7 = 7n - 7 + 1 = 7n - 6

The common difference = 22 - 15 = 7;

nth term = 1 + (n - 1)*7 = 7n - 7 + 1 = 7n - 6

Added 3/16/2016 6:44:53 PM

This answer has been confirmed as correct and helpful.

x^2(2x^3 - 3) - 3x(x + 4)

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 6x^2 - 12x

= 2x^5 - 3x^2 - 3x^2 - 12x

= 2x^5 - 6x^2 - 12x

Added 3/16/2016 11:52:16 PM

This answer has been confirmed as correct and helpful.

Work the item as directed.
Factor 24x2 - 6xy -63y2 completely.

Question

Not Answered

Updated 3/16/2016 8:58:05 PM

1 Answer/Comment

Factor completely the following quadratic expression.
9x2 + 24xy + 16y2

Question

Updated 3/16/2016 8:59:43 PM

1 Answer/Comment

32,737,446

questions answered

There are no comments.